Pelatihan Dasar Kecerdasan Buatan untuk Anak-Anak Padukuhan Ngepoh - Tok Se Ka; Alicia Bonita Putri Ch; Frindy Belens D. Sadow; Kezia Citra Denanta; Gideon Wahyu Winedar; Rendy Wijaya; Mario Louis Steven G. P.; Johannes P. Napitupulu; Permaha Richard Alexandre Petrusz; Ferdinandus Edwin Wiranata (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The rapid development of artificial intelligence technology must be introduced to prevent its misuse by humans. This training aims to increase interest and awareness of the impact and role of AI in daily life by providing a foundational understanding, fostering critical thinking in the use of AI-based technology. The training was conducted orally and practically through the delivery of simple material over three sessions for childrens aged 7-15 years with evaluations in the form of pre-test and post-test to measure understanding levels of artificial intelligence technology. The results showed a significant increase of 66,63% between pre-test and post-test scores, demonstrating that this training successfully enhanced the basic knowledge of children in Padukuhan Ngepoh regarding the interest and impact of artificial intelligence.